Games and simulations in distance learning: the AIDLET Model - Bidarra, José (2013)
This chapter discusses the selection and potential use of electronic games and simulations in distance learning supported by an operational model called AIDLET. After analyzing the different approaches to the use of games and simulations in education, and discussing their benefits and shortcomings, a framework was developed to facilitate the selection, repurposing, design and implementation of games and simulations, with focus on the practical aspects of the processes used in Open and Distance Learning (ODL). Whereas traditional learning is based on knowledge memorization and the comple- tion of carefully graded assignments, today, games, simulations and virtual environments turn out to be safe platforms for trial and error experimentation, i.e. learning by doing/playing. New instructional models may require that rich interactive processes of communication are supported, that assignments are structured as game-like projects, and that a culture of interaction, collaboration, and enablement drives learning and personal development. In this context, the AIDLET model was set out and verified against a taxonomy representing the main categories and genres of games to meet the requirements of distance education teachers, instructional designers and decision-makers.